Midwinter aggregation in the northern red-backed vole, Clethrionomys rutilus - West, Stephen D. (Canadian Journal of Zoology, 1977)
Livetrapping in black spruce (Picea mariana) taiga 60 km north of Fairbanks, Alaska, during 1972–1973 revealed that the dispersion pattern of the capture points for a population of northern red-backed voles varied greatly with season. The population was distributed without apparent aggregation from midsummer (July) until early winter (mid-November). During midwinter all animals were found in one section of the trapping grid. In early spring (April) the voles moved apart, and by May they appeared once more evenly distributed. The composition and structure of vegetation inside and outside of the area of aggregation was analyzed, and a significantly thicker moss layer was found within the area of aggregation. Possible advantages and disadvantages of the midwinter aggregation to individual voles are discussed. It is suggested that habitat limitation in terms of a short supply of suitable overwintering sites is a reasonable explanation for the observed aggregation.